Digital Interventions at Scale: Lessons from NPTEL and IIT Madras B.S. Degree Program. - WARRIEM, JAYAKRISHNAN; THANGARAJ, ANDREW; MUKUND, MADHAVAN; BALAJI, BHARATHI (Communications of the ACM, 2022)
The article discusses online learning in higher education in India, with particular focus given to two successful initiatives including the National Program on Technology Enhanced Learning (NPTEL) and the B.S. program in Programming and Data Science (PDS). Both programs are offered by the Indian Institute of Technology (IIT) Madras in Chennai, India, which is funded by the Ministry of Education. Topics include access to quality education, course offerings, and lessons learned from implementing such programs.